Micropatterned Devices: Climbing Plant‐Inspired Micropatterned Devices for Reversible Attachment (Adv. Funct. Mater. 38/2020). (17th September 2020) - Fiorello, Isabella; Tricinci, Omar; Naselli, Giovanna Adele; Mondini, Alessio; Filippeschi, Carlo; Tramacere, Francesca; Mishra, Anand Kumar; Mazzolai, Barbara
Abstract : In article number 2003380, Isabella Fiorello, Barbara Mazzolai, and co‐workers develop innovative climbing plant‐inspired flexible micro‐patterned devices for reversible attachment using a two‐photon lithography system. The microfabricated devices demonstrate strong interlocking over a wide range of rough surfaces, such as abrasive materials, fabrics with different textures, and soft skin tissues. Furthermore, the high shear‐dependent microfabricated devices show great potential for climbing robot applications, especially in soft‐ and micro‐robotics.